Mycobacteroides chelonae-abscessus group infection in a Paraguayan rainbow boa (Epicrates crassus) - Simões, Sarah Raquel Jesus Santos; Ferreira-Machado, Eduardo; Garcia, Jamile Macedo; Ervedosa, Ticiana Brasil; Navas-Suárez, Pedro Enrique; Jesus, Isis Paixão de; Carvalho, Julia de; Gagliotti, Gabrielle Fernanda Pereira da Silva; Ressio, Rodrigo Albergaria; Cirqueira, Cinthya dos Santos; Figueiredo, Ketlyn Bolsachini; Carvalho, Ana Carolina Souza Ramos de; et al. (Brazilian Journal of Veterinary Pathology, 2023)
Paraguayan rainbow boa (Epicrates crassus) is widely distributed in the central portion of South America, threatened by human actions, and commonly maintained as a pet or in scientific collections. Mycobacteroides chelonae-abscessus group (MCABC) is the most important emerging nontuberculous mycobacterium pathogen in humans. This report describes a systemic MCABC infection in a captive E. crassus, with heterophilic granulomatous lesions in the lungs, liver, kidneys, and peripheral nervous system. Histochemical stains demonstrated Gram-positive and alcohol-acid-fast bacilli that cross-reacted with antigens of Bacillus Calmette-Guérin in immunohistochemistry. A nested polymerase chain reaction followed by DNA sequencing indicated the genus of the mycobacteria. Despite the rapid systemic spread of MCABC, it is necessary to develop safer, more rapid, and more effective treatments and diagnoses to understand the role of reptiles in this disease.